Developing tools as plug‐ins: TOPI 2012 special issue. (7th January 2014) - Garbervetsky, Diego; Kim, Sunghun; Garbervetsky, Diego; Kim, Sunghun
SUMMARY Our knowledge as to how to solve software engineering problems is increasingly being encapsulated in tools. These tools are at their strongest when they operate in a preexisting development that can provide integration with existing elements such as compilers, debuggers, profilers, and visualizers as well as numerous other development and, often, runtime tools. However, building tools as plug‐ins can be challenging and raise many questions: How do they interact with the core environment? How do they interact with other existing plug‐ins, especially as each developer may choose a different set of plug‐ins. How can we share tools across different and future core development environments? How do we evaluate the usefulness of the tools? The series of workshops on Developing Tools as Plug‐ins (TOPI) tries to address these questions. Researchers are invited to present position papers spotting the medium‐term and long‐term challenges of developing tools as plug‐ins as well as research contributions identifying recent successful tools as plug‐ins, characteristics of good plug‐ins and reports of the main difficulties in implementing plug‐ins in current platforms. This issue includes extended versions of the best papers presented at TOPI 2012. Copyright © 2014 John Wiley & Sons, Ltd.